P573Added diagnostic value of multiplex ligation-dependent probe amplification of plakophilin-2 in arrhythmogenic cardiomyopathy. (15th July 2014) - Lazzarini, E; Rigato, I; Jongbloed, JD; Celeghin, R; Cason, M; Carturan, E; Thiene, G; Basso, C; Pilichou, K; Van Tintelen, JP
Abstract: Background: Arrhythmogenic Cardiomyopathy (ACM) is an inherited myocardial disease characterized by fibro-fatty replacement of myocardium. Patients are at risk of ventricular arrhythmias and sudden death. Screening of desmosomal genes currently results in a diagnostic yield of about 50%. Aim: The aim of this study is to investigate whether detection of large deletions/duplications of the plakophilin-2 gene (PKP2) increase the yield of genetic screening in ACM. Methods: 60 index cases with a clinical diagnosis of ACM consecutively enrolled at our referral center underwent bidirectional sequencing using ABI-PRISM 3730 (Life Technologies) for all desmosomal-encoding genes. Genotype-negative patients were additionally screened for copy number variations (CNVs) in PKP2 by Multiplex Ligation-dependant Probe Amplification (MLPA) using SALSA MLPA kit P168 ARVC-PKP2 (MRC-Holland) and by quantitative Real-Time PCR on a Roche Light Cycler 480 platform. Results: Conventional sequencing of the ACM patients identified disease-causing nucleotide variants in 36 of the 60 ACM-patients (60%); 8% (n=5) of the cohort presented mutation in Desmoglein-2 gene, 23% (n=14) in Desmoplakin, 12% (n=7) in PKP2, 3% (n=2) in Desmocollin-2, 3% in Plakoglobin (n=2) whereas 10% (n=6) were multiple mutations carriers. MLPA analysis successfully identified a heterozygous deletion of exon 4 in an otherwise genotype-negative case, which was further confirmed by qPCR analysis showing a reduction of PKP2 copy number when compared to control samples. Conclusions: This study highlights the potential of increasing the diagnostic genetic yield - in our population by nearly 2% for just one gene- by searching CNVs in ACM patients. This will be also achieved by extending the analysis to all ACM disease-causing genes as well as to genotype-positive patients.